2017
DOI: 10.2183/pjab.93.021
|View full text |Cite
|
Sign up to set email alerts
|

Organization and dynamics of yeast mitochondrial nucleoids

Abstract: Mitochondrial DNA (mtDNA) is packaged by association with specific proteins in compact DNA-protein complexes named mitochondrial nucleoids (mt-nucleoids). The budding yeast Saccharomyces cerevisiae is able to grow either aerobically or anaerobically. Due to this characteristic, S. cerevisiae has been extensively used as a model organism to study genetics, morphology and biochemistry of mitochondria for a long time. Mitochondria of S. cerevisiae frequently fuse and divide, and perform dynamic morphological chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 114 publications
(141 reference statements)
1
41
1
Order By: Relevance
“…To monitor the spatial distribution and stability of mtDNA within nucleoids in vivo, we used DAPI staining of DNA in combination with fluorescent live-cell imaging ( Williamson and Fennell, 1975 ). WT cells showed a mean of approximately eight discrete mtDNA foci per cell during growth, consistent with previous data ( Chen and Butow, 2005 ; Miyakawa, 2017 ), and maintained this number over 5 d of starvation ( Fig. 1, C–E ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To monitor the spatial distribution and stability of mtDNA within nucleoids in vivo, we used DAPI staining of DNA in combination with fluorescent live-cell imaging ( Williamson and Fennell, 1975 ). WT cells showed a mean of approximately eight discrete mtDNA foci per cell during growth, consistent with previous data ( Chen and Butow, 2005 ; Miyakawa, 2017 ), and maintained this number over 5 d of starvation ( Fig. 1, C–E ).…”
Section: Resultssupporting
confidence: 91%
“…In Saccharomyces cerevisiae , the ∼85-kb mitochondrial DNA (mtDNA) encodes for eight proteins, including seven essential respiratory chain subunits, transfer and ribosomal RNAs, and the RNA subunit of RNase P ( Foury et al, 1998 ; Turk et al, 2013 ). The 20–100 mtDNA copies per yeast cell are packaged into multiple dynamic nucleoprotein complexes, termed nucleoids, that remodel in number, distribution, protein composition, and mtDNA content (1–10 copies) in response to metabolic cues ( MacAlpine et al, 2000 ; Kucej et al, 2008 ; Miyakawa, 2017 ). mtDNA replication occurs independently of the nuclear genome throughout the cell cycle but coordinates with mitochondrial division to distribute nucleoids within the network of mitochondria ( Meeusen and Nunnari, 2003 ; Murley et al, 2013 ; Lewis et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The discoveries that mtDNA molecules are packaged into protein–DNA complexes, designated nucleoids , in Physarum (Kuroiwa, Kitane, Watanabe, & Kawano, ) and that a HMG ‐like protein is present in yeast mitochondria (Caron, Jacq, & Rouviere‐Yaniv, ) were the first clues to this problem. Subsequent biochemical analyses demonstrated that yeast mitochondrial nucleoids contain a variety of other nuclear‐encoded proteins in addition to the HMG‐like protein encoded by ABF2 (see Table ), Those include the gamma DNA polymerase encoded by MIP1 , the mitochondrial RNA polymerase encoded by RPO41 , the single‐strand DNA‐binding protein encoded by RIM1 , the repair protein encoded by MGM1 , the Hsp10, Hsp60 and Hsp70 chaperonins, and some proteins of the mitochondrial ribosome (Chen & Butow, ; Miyakawa, ). In these complexes, mtDNA molecules are bent by their contact with ABF2 proteins, which, on average, distribute one ABF2 molecule per 15–30 bp of DNA with a preference for GC‐rich sequences.…”
Section: Molecular Bases Of Mitochondrial Inheritance: Replication Rmentioning
confidence: 99%
“…To circumvent this problem, the mtDNA is compacted into condensed nucleo-protein structures called mitochondrial nucleoids (mt-nucleoids) [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Considering the diameter of the mt-nucleoids in S. cerevisiae (0.3–0.6 μm) [ 24 ], yeast mtDNA must undergo a compaction of roughly three orders of magnitude.…”
Section: Mitochondrial Dna Forms Higher-order Structures Called MImentioning
confidence: 99%